TEACHING SCIENCE THROUGH TELEVISION - Ray, Hiranmay (SCHOOL SCIENCE, 2013)
We are living in a world of science. In every sphere around us we can feel and see as well the terrific impact of science and technology. With the tremendous progress of science and technology, it has become necessary for every man to understand and apply science to his day-to-day life. Contents of study have increased to a great extent. Teachers have to teach and the students have to understand more matter in a given period than they used to do previously. The concept of education has undergone a change. It is not merely the understanding and memorising a body of facts, but is considered to be a process which prepares an individual to become a worthy member of the society. For educating children for life, improvisation of teaching techniques with the help of audio-visual aids has become necessary. Audio-visual aids which include sound films and televisions, are considered to be the most important of all teaching aids. Television is one of the most significant discoveries of recent times in the field of communication.